The Impact of Consumer Satisfaction on Brand Building of Rural Health Industry in Sichuan from the Perspective of Silver Economy - Jingxin Cao; Jacky Mong Kwan Watt (International Journal of Economics, Commerce, and Management, 2025)
This research explores the impact of consumer satisfaction on brand building within the rural health industry in Sichuan, focusing specifically on the elderly population in the context of the silver economy. It identifies key factors influencing consumer satisfaction, including quality of service, customer support, and community engagement. The study highlights how high-quality healthcare tailored to the needs of older adults fosters trust and loyalty, while adequate customer support enhances the overall experience by addressing specific concerns. Furthermore, community engagement creates a sense of belonging, increasing health service satisfaction. The findings suggest that healthcare providers can strengthen their brand by prioritizing these elements, leading to better health outcomes and increased consumer loyalty among 375 local Sichuan senior citizens